2017
DOI: 10.1002/pts.2320
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Tenax® as a Simulant for the Migration of Contaminants in Dry Foodstuffs: A Review

Abstract: Packaging materials are found to represent a source of contamination through the migration of substances from the packaging into the foodstuff. As a response to an increasing number of food‐safety issues, research on the migration of chemicals from packaging materials into foodstuffs is being conducted. Moreover, packaging materials are tested for the migration of chemicals through migration experiments, using food simulants. EU Regulation N°10/2011 on plastic materials and articles intended to come into conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…The major factors governing the migration of constituents into food are the physicochemical properties (density, crystallinity, cross-linking, branching, and glass transition temperature) of the packing materials, the nature of the migratory species, the quality of the simulant (size, shape, and charge), and temperature. , Bioplastic fibers [GA (U), GA (P), and GA (γ)] were tested with regard to migration of components into a food stimulant such as Tenax, so as to mimic the migration into dry foods, e.g., cereal. The observed food contact migration values for GA (U), GA (γ), and GA (P) were determined to be 4.8 ± 1.2, 4.2 ± 0.9, and 3.0 ± 0.8 mg/dm 2 , respectively. Results indicated that, for all three bioplastic variations tested, the migration intensities are under the limit (below 10 mg/dm 2 ) set by European Union legislation .…”
Section: Resultsmentioning
confidence: 99%
“…The major factors governing the migration of constituents into food are the physicochemical properties (density, crystallinity, cross-linking, branching, and glass transition temperature) of the packing materials, the nature of the migratory species, the quality of the simulant (size, shape, and charge), and temperature. , Bioplastic fibers [GA (U), GA (P), and GA (γ)] were tested with regard to migration of components into a food stimulant such as Tenax, so as to mimic the migration into dry foods, e.g., cereal. The observed food contact migration values for GA (U), GA (γ), and GA (P) were determined to be 4.8 ± 1.2, 4.2 ± 0.9, and 3.0 ± 0.8 mg/dm 2 , respectively. Results indicated that, for all three bioplastic variations tested, the migration intensities are under the limit (below 10 mg/dm 2 ) set by European Union legislation .…”
Section: Resultsmentioning
confidence: 99%
“…The European Food Safety Authority (EFSA) has created a document about the migration from non-plastic food contact materials [23]. Paper and board can be treated as monolayer plastic packaging materials because the diffusion rate decreases with the increase in the molecular weight of the migrants [ 24] although the transfer into the foodstuff could happen much faster in the paper material than the migration from plastics [16].…”
Section: A C C E P T E D Mmentioning
confidence: 99%
“…On the other hand, Tenax should not be recommended as a food simulant for temperature up to 150ºC. In this case, the adsorbent Porapak could be used [16,17,18]. The European Reference Laboratory for Food Contact Materials (EURL-FCM) performed an…”
Section: Introductionmentioning
confidence: 99%
“…Eicher et al 30 have already postulated that there are differences in the sorption power of materials due to differences in particle size (distribution), material and porosity. van den Houwe et al 35 A more detailed look on the data revealed a shift in the ratio between the fractions towards less volatile substances when using enhanced temperatures, which might lead to an overestimation of the migration under some circumstances. As a result, we recommended against using test conditions with temperatures > 40 C without a profound knowledge of the underlying 'real-life' transport processes.…”
Section: Migration Into Tenaxmentioning
confidence: 99%